Rancang Bangun Monitoring dan Pengendali Suhu, pH dan Kekeruhan Air pada Smart Akuarium - Utami, Amalia Rizqi; Erlangga, Muhamad; Sugiarto, Kharis (LPPM ITK, 2024)
Fish is a food source that is easily obtained in Indonesia, fish can not only be found in rivers and the sea. Along with developments in technology, fish can be cultivated at home with limited land. In fish farming, water quality has a major influence on fish production. There are several parameters that can be used as a reference to determine whether water is said to have good quality, namely temperature, pH and water turbidity. In this research, ESP32 is used as a microcontroller to process the readings of the temperature sensor DS18B20, pH sensor and TDS sensor in the aquarium, with data that can be monitored via LCD and smartphone. This tool can set the pump ON/OFF based on predetermined water condition parameters. The comparison results between aquariums that use smart aquariums and aquariums that do not use smart aquariums show that using smart aquariums is more effective in maintaining water quality (pH 6.8, temperature 29.4ºC, turbidity 96 ppm) compared to not using smart aquariums (pH 3.5, temperature 28.9ºC, turbidity 178 ppm). Using a smart aquarium is also more efficient because it only consumes an average of 64.6 watts per day with a monthly cost of IDR 2,798, compared to a continuous pump which consumes 324 watts per day with a monthly cost of IDR 14,035. So pumps controlled by smart aquariums can better maintain water quality and save electricity costs.